The Struggle for Greek independence (Hamden, Connecticut)
vi, [1], 259 sayfa
Keywords: “With two exceptions the essays printed in this collection are based on papers read at a seminar organised under the auspices of the History Department of the School of Slavonic and East European Studies and the Department of Byzantine and Modern Greek Studies, King's College, University of London. The seminar was held during the winter term 1971“ -- iç kapak arkası.